Rapeseed (Brassica napus) Mitogen-Activated Protein Kinase 1 Enhances Shading Tolerance by Regulating the Photosynthesis Capability of Photosystem II - Wang, Zhen; Liu, Miao; Yao, Mengnan; Zhang, Xiaoli; Qu, Cunmin; Du, Hai; Lu, Kun; Li, Jiana; Wei, Lijuan; Liang, Ying (Frontiers in Plant Science, 2022)
Rapeseed (Brassica napus) is the third-largest source of vegetable oil in the world with an edible, medicinal, and ornamental value. However, insufficient light or high planting density directly affects its growth, development, yield, and quality. Mitogen-activated protein kinases (MAPKs) are serine/threonine protein kinases that play key roles in regulating the responses to biotic and abiotic stresses in plants. In this study, we found that the promoter of BnaMAPK1 contained several light-responsive elements (including the AT1-motif, G-Box, and TCT-motif), consistent with its shading stress-induced upregulation. Compared with the wild type under shading stress, BnaMAPK1-overexpressing plants showed higher light capture efficiency and carbon assimilation capacity, enhancing their shading tolerance. Using RNA sequencing, we systematically investigated the function of BnaMAPK1 in shading stress on photosynthetic structure, Calvin cycle, and light-driven electron transport. Notably, numerous genes encoding light-harvesting chlorophyll a/b-binding proteins (BnaLHCBs) in photosystem II-light-harvesting complex (LHC) II supercomplex were significantly downregulated in the BnaMAPK1-overexpressing lines relative to the wild type under shading stress. Combining RNA sequencing and yeast library screening, a candidate interaction partner of BnaMAPK1 regulating in shading stress, BnaLHCB3, was obtained. Moreover, yeast two-hybrid and split-luciferase complementation assays confirmed the physical interaction relationship between BnaLHCB3 and BnaMAPK1, suggesting that BnaMAPK1 may involve in stabilizing the photosystem II–LHC II supercomplex. Taken together, our results demonstrate that BnaMAPK1 positively regulates photosynthesis capability to respond to shading stress in rapeseed, possibly by controlling antenna proteins complex in photosystem II, and could provide valuable information for further breeding for rapeseed stress tolerance.